Opening Ratio for Canine & Molar Area in Relation to Incisor - Rashmi Gangavati, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The modification of OVD is a procedure that is regarded as both important and significant in the area of prosthodontics. Incorrect estimation of the space available between opposing teeth may lead to an improper framework design. Aim: To determine and assess the average opening ratio in the canine and molar area in relation to the extent of opening in the incisor area. Material & method: Intra oral scans of 34 participants were made using Medit i500 intraoral scanner. After mounting the virtual casts the central incisors were opened between 0 to 5mm and thereby analyses of the openings were checked in the canine and first molar region. Result: On evaliation with Karl Pearson’s statistical test and plotted them on the scatter diagrams. The average ratio of incisor opening to that in the canine region (I:C) was 1.10 and the average incisor opening to molar ratio (I:M) was nearly 1.55. Conclusion: The average ratio of incisor opening to that in the canine region is 1.10 and the average incisor opening to molar ratio is nearly 1.55.